Analisis Work-Life Balance, Quality of Worklife, Happiness on Work dan Emotional Stability terhadap Kinerja Barista di Coffeeshop Kota Madiun - Asmike, Metik; Hasanah, Karuniawati; Raras Swastika Sistyo Maharani (Yayasan Cita Cendikiawan Al Kharizmi, 2025)
The research results show that (1) partially the work life balance variable (X1) has a positive and significant influence on barista performance, partially the Quality of worklife (X2) has a positive and significant influence on barista performance, happines at work variable (X3) has a positive and significant influence on barista performance ,partially the emotional stability variable (X4) has a positive and significant influence on the performance of baristas in Madiun city.